Context Specificities in Entrepreneurship Research - Jaim, Jasmine; Islam, Mohammad Nazmul (Journal of Entrepreneurship, Business and Economics; Vol 6 No 1 (2018), 2018)
Research in entrepreneurship is mostly concentrated on two specific developed areas – Europe and North America. Investigation in other parts of the world is extremely limited, whereas entrepreneurship is potentially contributing to these economies. To comprehend entrepreneurship in a more nuanced way, researchers have already made calls to incorporate context specific aspects of comparatively under explored regions, that can be absent in or substantially different from the western developed economies. Yet to date, there is no systematic analysis to explore how context specificities of these regions are contributing to the extant literature by providing insightful findings. With a notion to advance the understanding of entrepreneurship research, based on a comprehensive literature review, this article identifies the key contextual features of the existing studies, and building upon the critical analysis, it demonstrate a way forward. Literature review Keywords: Entrepreneurship, Small Businesses, Micro-businesses, Context, Context Specific Aspects Reference to this paper should be made as follows: Jaim, J., & Nazmul Islam, M. (2018). Context Specificities in Entrepreneurship Research, Journal of Entrepreneurship, Business and Economics , 6 (1), 59–77.